2011
DOI: 10.1002/bit.24382
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of IGF‐I from a biodegradable matrix improves functional recovery of skeletal muscle from ischemia/reperfusion

Abstract: Ischemia/reperfusion (I/R) injury is a considerable insult to skeletal muscle, often resulting in prolonged functional deficits. The purpose of the current study was to evaluate the controlled release of the pro-regenerative growth factor, insulin-like growth factor-I (IGF-I), from a biodegradable polyethylene glycol (PEG)ylated fibrin gel matrix and the subsequent recovery of skeletal muscle from I/R. To accomplish this, the hind limbs of male Sprague–Dawley rats were subjected to 2-h tourniquet-induced I/R t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
4
48
0
Order By: Relevance
“…Hydrogels are one type of matrix widely used to deliver cells for muscle regeneration [36]. These include collagen [37], alginate [38], fibrin [35,39], hyaluronic acid [40], and poly(ethylene glycol) [41]. Hydrogel modulus may be used to induce stem cell myogenic differentiation.…”
Section: Introductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are one type of matrix widely used to deliver cells for muscle regeneration [36]. These include collagen [37], alginate [38], fibrin [35,39], hyaluronic acid [40], and poly(ethylene glycol) [41]. Hydrogel modulus may be used to induce stem cell myogenic differentiation.…”
Section: Introductionsmentioning
confidence: 99%
“…A potential approach to increase myogenic differentiation is to deliver stem cells using suitable matrix, where matrix property itself and/or loaded biomolecules induce myogenic differentiation [34,35]. Hydrogels are one type of matrix widely used to deliver cells for muscle regeneration [36].…”
Section: Introductionsmentioning
confidence: 99%
“…Growth factor concentrations varied significantly across the studies as well as for the individual growth factors used (VEGF: 1-3 μg; IGF: 6-10 μg; bFGF: 5 ng to 100 μg; HGF: 5 ng to 100 μg). Table 2 also highlights the relatively small number of studies (4/12 studies) that reported the degree of functional regeneration after treatment (rather than just tissue reconstitution), and 3 of them were conducted in hind limb ischemia injury models [Borselli et al, 2010;Hammers et al, 2012;Rybalko et al, 2015b]. There was only 1 study (1/12) in which growth factor-based repair studies evaluated functional recovery in a VML injury model [Grasman et al, 2015].…”
Section: Growth Factor-based Tissue Engineering Approaches For Skeletmentioning
confidence: 99%
“…A wide range of cytokines, growth factors and other bioactive molecules have been found to be essential for supporting the viability and differentiation of stem cells alongside the skeletal myogenic lineage. The most effective bioactive molecules in this context are myogenic growth factor IGF-1 and angiogenic growth factor VEGF; they both have been reported to positively influence muscle cell populations in vitro and in vivo [71,72,123,135].…”
Section: Delivery Of Bioactive Moleculesmentioning
confidence: 99%